A Total systems study on Richmark Food Inc. - Dato, Czarina T.; Luy, Don AMrk; Tan, John Vincent U.; Velasquez, Katherine May G. (College of Engineering, 2003)
Competition in the market and the industry sets a need for companies to assess or review their corporate strategy. It is also a competition that companies aim to set their goals or mission and vision to direct their organization in a profitable and marketable situation in the long ruin. Richmarks Food Incorporated (RFI), the company under study is engaged in the production of Bihon noodles. It is the company's goal to expand their product lines or operations in the future to make their company the number one in their field. To do so, the company has to clearly define their mission and vision, set their long-term and operational strategy and run its manufacturing excellence in full extent. In line with assessing the organization and improving the production system of RFI, a study was conducted to address the managerial and operational concerns of the company. The study aimed at determining the long-term goals of the company to be able to set the appropriate strategies to support their mission and vision, which is to increase the market share of the product and to expand operations in the future. The study also aimed at identifying the major problems that the company encounters regarding the total system of RFI's plant in Bulacan so that the plant can support the strategies set by the country. Strategies were outlined in the study based on the considerations of the company's strength and weaknesses, the opportunities and threats posed by the competitors and other external factors. Among the strategies outlined in this study is to increase the branded Bihon products from 5-20 percent to make the brand name of RFI (Happy) known to market before the introduction of instant noodles (new product of the company); pursue ISO 9000 certification and environmental compliance certification; form a Research and Development Team that will handle the development of instant products; plan for the redesigning of layout to accommodate the future expansions and in compliance with ISO standards; and plan a new production schedule in anticipation of the increase in production volume and product line expansion. Three problems were identified to be hindrances in implementing the strategies deemed appropriate for the company. These are the inappropriate features of the Drying machine, inefficiencies in the layout of the plant and the lack of standard operating procedures. Product buildup, the occurrence of spots and noodle breakage can be attributed to the inappropriate dryer features. While the company may have come up with some remedial actions like the humidification process, the end result can still be improved. A new dryer design (parallel current tunnel dryer) is introduced to address these problems. The new dryer is expected to reduce the drying time to 160 minutes, reduce optimal dryer capacity by 33%, recycle 44% of the heated air thereby reducing energy consumption by 18.6% and increasing the overall production capacities by 50%. Pilot testing on a smaller scale is needed to be performed in order to verify the expected results. Inefficiencies in the layout problem were addressed by conducting a product/process match to determine at what areas or factors the layout should be improved on. Changes on the layout were made by combining the two drying machines and placing it outside the Plant Area and reorienting the steam conveyor to accommodate the Setting Area in the area adjacent to the Cutting area. This recommendation has reduced the processing time by 21.19% and the distance traveled by materials by 44.14%. All cost associated with the new layout can be recovered only in 2 months of operation. The lack of Standard Operating Procedures was addressed by identifying the performance measures appropriate for the plant operations. An Implementation guideline was outlined for the company to follow to serve as basis for their standard operating procedures. One of the company's goals is to apply for the environmental compliance certification. The company currently uses a lagoon as its wastewater treatment process. However, the resulting BOD5 and SS content of the production plant effluent is beyond the limit set by the DENR. A new wastewater system is recommended. This system is expected to recover about 75% of the raw material lost in the noodle production and process it to produce corn meal that can be sold at 300 to 350 pesos per sack. In addition, the resulting effluent quality is good enough that it can be reused in noodle processing thereby reducing water consumption by around 60%. Addressing the problems mentioned above will prepare the company in implementing their strategies and in achieving their mission and vision.